PERILAKU KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MEMBENTUK KOMPETENSI PROFESIONALISME GURU - Azizah, Kuni (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
Based on the problems that exist in the world of education, there is a need for the role of the principal as a supervisor to foster teachers to become professional educators. However, from within a teacher must also have a strong will to be more professional so that the goals of an education can be easily achieved. Professional teachers are not only required to master the material but the teacher can develop teaching materials, learning methods, can motivate students and have high insight in the world of education. Professional teachers cannot be separated from the role of a principal as a supervisor. A supervisor must be able to foster, provide direction and motivate teachers, this supervisor's behavior can shape the competence of teachers to become more professional teachers. The method used in writing this study uses library research or literature study by collecting data from books and journals related to supervisor behavior in shaping teacher professional competence.